Evaluation of Some Biochemical Variables in Pregnant Women who Have Aborted in The Third Month - Shaker , Asmaa Hashim; Mahmood, Methaq Nazhan; Al-doori, Ameerah Abdulmunem Yaseen (American Journal of Biology and Natural Sciences, 2026)
The study aims to estimate some of the biochemical variables associated with pregnant women who aborted in the first months of pregnancy compared to healthy women and the relationship of these variables to early abortion.This includes measurement of prothrombin time, partial prothrombin time, International Normalized Ratio (INR), estrogen measurement, and measurement of glutathione and malondialdehydein the blood serum of the groups under study.The current study is designed by taking 130 blood samples from females.The samples are divided into two groups, the first is the healthy group as a control group including 70 samples from healthy women, and the second is the group of patients with aborted pregnant women in the third month of pregnancy which includes 60 samples with their ages ranging between 35-45 years. Prothrombin time (Pt) and partial prothrombin time (Ptt) measurements, as well as the International Normalized Ratio (INR), were significantly higher in the group of women who had abortions than in the control group of healthy women, according to the current study's findings. The findings also show that, in comparison to the control group of healthy women, the group of aborted women had significantly higher levels of estrogen and lower levels of glutathione.